Analysis of Phrases Based on their Forming Elements in the Film Langit Tak Selamanya Abu-Abu by Kemendikbud RI - Tirza Marshanda; Alina Hidayatul; Jihanita Rindu; Miftahul Jannah; Oktian Oxana; Rakha Pratama; Rihada Aisy; Siti Salamah; Yuliva Rumboy; Raheni Suhita (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this study is to analyze the film